Sarco‐Model: A score to predict the dropout risk in the perspective of organ allocation in patients awaiting liver transplantation. (22nd April 2021) - Lai, Quirino; Magistri, Paolo; Lionetti, Raffaella; Avolio, Alfonso W.; Lenci, Ilaria; Giannelli, Valerio; Pecchi, Annarita; Ferri, Flaminia; Marrone, Giuseppe; Angelico, Mario; Milana, Martina; Schinniná, Vincenzo; et al.
Abstract: Background & Aims: Sarcopenia in liver transplantation (LT) cirrhotic candidates has been connected with higher dropouts and graft losses after transplant. The study aims to create an 'urgency' model combining sarcopenia and Model for End‐stage Liver Disease Sodium (MELDNa) to predict the risk of dropout and identify an appropriate threshold of post‐LT futility. Methods: A total of 1087 adult cirrhotic patients were listed for a first LT during January 2012 to December 2018. The study population was split into a training (n = 855) and a validation set (n = 232). Results: Using a competing‐risk analysis of cause‐specific hazards, we created the Sarco‐Model2 . According to the model, one extra point of MELDNa was added for each 0.5 cm 2 /m 2 reduction of total psoas area (TPA) < 6.0 cm 2 /m 2 . At external validation, the Sarco‐Model2 showed the best diagnostic ability for predicting the risk of 3‐month dropout in patients with MELDNa < 20 (area under the curve [AUC] = 0.93; P  = .003). Using the net reclassification improvement, 14.3% of dropped‐out patients were correctly reclassified using the Sarco‐Model2 . As for the futility threshold, transplanted patients with TPA < 6.0 cm 2 /m 2 and MELDNa 35‐40 (n = 16/833, 1.9%) had the worse results (6‐month graft loss = 25.5%). Conclusions: In sarcopenic patients with MELDNa < 20, the 'urgency' Sarco‐Model2 should be used to prioritize the list, while MELDNa value should be preferred in patients with MELDNa ≥ 20. The Sarco‐Model2 played a role in more than 30% of the cases in the investigated allocation scenario. In sarcopenic patients with a MELDNa value of 35‐40, 'futile' transplantation should be considered.